The Multiple Roles of Fibroblast Growth Factor in Diabetic Nephropathy - Deng J; Liu Y; Liu Y; Li W; Nie X (Dove Medical Press, 2021)
Junyu Deng,1 Ye Liu,1 Yiqiu Liu,1 Wei Li,1,2 Xuqiang Nie1- 4 1College of Pharmacy, Zunyi Medical University, Zunyi, 563000, People's Republic of China; 2Joint International Research Laboratory of Ethnomedicine of Chinese Ministry of Education, Zunyi Medical University, Zunyi, 563000, People's Republic of China; 3Key Laboratory of the Basic Pharmacology of the Ministry of Education, Zunyi Medical University, Zunyi, 563000, People's Republic of China; 4Institute of Materia Medica, College of Pharmacy, Third Military Medical University (Army Medical University), Chongqing, 400038, People's Republic of ChinaCorrespondence: Xuqiang NieCollege of Pharmacy, Joint International Research Laboratory of Ethnomedicine of Chinese Ministry of Education, Zunyi Medical University, Zunyi, 563000, People's Republic of ChinaTel +86-0851-2864-2516Email niexuqiang@zmu.edu.cnAbstract: Diabetic nephropathy (DN) is a common microvascular complication in the late stages of diabetes. Currently, the etiology and pathogenesis of DN are not well understood. Even so, available evidence shows its development is associated with metabolism, oxidative stress, cytokine interaction, genetic factors, and renal microvascular disease. Diabetic nephropathy can lead to proteinuria, edema and hypertension, among other complications. In severe cases, it can cause life-threatening complications such as renal failure. Patients with type 1 diabetes, hypertension, high protein intake, and smokers have a higher risk of developing DN. Fibroblast growth factor (FGF) regulates several human processes essential for normal development. Even though FGF has been implicated in the pathological development of DN, the underlying mechanisms are not well understood. This review summarizes the role of FGF in the development of DN. Moreover, the association of FGF with metabolism, inflammation, oxidative stress and fibrosis in the context of DN is discussed. Findings of this review are expected to deepen our understanding of DN and generate ideas for developing effective prevention and treatments for the disease.Keywords: fibroblast growth factor, diabetic nephropathy, signaling pathways, pharmacological action, renal fibrosis